Strategi Pengembangan Keberagamaan Peserta Didik Sekolah Menengah Atas - Shafa, Ichwan; Ulpah, Ghina; Huda, Miftahul; Muhtadin (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2024)
In the context of Islamic religious education, there are some that are vertical and some that are horizontal. The creation of a vertical religious atmosphere can be realized in worship activities. Meanwhile, the creation of a horizontal religious atmosphere places the school as a social institution, which, when viewed from the structure of the relationship between humans, can be classified. The form of business carried out by schools in improving the religious attitudes of students is to carry out Islamic activities. This research method uses literature review research. The research method is literature review or literature study, which contains theories relevant to research problems. The instrument used is descriptive analysis. Based on the findings of the analysis from the literature review, the author will review this paper in the form of an article with a detailed discussion of the Implementation of High School Students' Religious Development. Implementation of the diversity of high school students is an effort carried out systematically in the form of guidance, providing information, supervision and also control to improve the quality of students, especially in terms of religion in creating mental attitudes and developing positive potential so that there is good diversity in students.